The Ethical Behaviors Of Educational Leaders In Ethiopian Public Universities: The Case Of The Western Cluster Universities - Amsale, Frew; Bekele, Mitiku; Tafesse, Mebratu (European Scientific Journal, ESJ, 2016)
The purpose of this study was to assess the extent to which educational leaders in the western cluster public universities of Ethiopia are ethical. Ethical leadership variables such as fairness, equity, multicultural competence, modeling ethical behaviors and altruism are considered in describing the ethical behaviors of the leaders. Descriptive survey research design with quantitative method was employed for it fits the purpose of the study. Data was collected from instructors and educational leaders holding various leadership positions in the sample universities. Accordingly, 107 instructors, 12 department heads, 6 college deans, 2 academic quality assurance officers, 3 ethical officers, 1 vice president and 1 president participated in the study. Questionnaires were mainly used to collect data from the respondents. T-test and ANOVA, among other data analysis tools, were used to analyze the data. The results of the study revealed that leaders in the sample universities practice ethical leadership moderately. The leaders failed to demonstrate the ethical leadership practices to the expected level. They have been found to demonstrate low multicultural competence, low at altruism, and low at modeling ethical behavior. And hence, it could be concluded that the educational leaders in public universities failed to meet the standards and expectations of ethical leadership. As a result, it is recommended that the academic leaders in the public universities need to be provided with leadership development opportunities. Moreover, public universities can establish leadership development programs that will enable leaders to continually update themselves and practice ethical leadership to the expected level.